(untitled) (Journal of Pharmaceutical Negative Results, 2022)
According to the 3rd WHO methods, normal sperm morphology has been considered to be directly related with the fertilization process and pregnancy. The quality of semen such as sperm morphology, count, and motility has been reduced due to abnormalities in male thus, causing infertility. A considerable factor responsible for infertility among male partners may be as a result of microbial contamination. Semen may contain contamination while collecting sample. However, there are some sperm preparation techniques that can be used for the removal of contamination in semen such as; swim up, density gradient, simple wash, discontinuous density gradient. The main objective of this study is to find out the presence of infections and microbial contamination. This study will compare sperm count and sperm motility of patient’s semen sample with numbers of debris/ present infectious agent. Microbiological assay of semen sample will be performed. Also, various infectious agents causing infertility will be evaluated and studied. Semen analysis, semen preparation by density gradient, semen culture were carried out to look into the effect of microbial contamination on semen sample of infertile men.